Development of Powerpoint-Based Learning Media on Learning Aqeedah Morals - Lufita Sari Sitorus; Mardianto Mardianto; Hasan Matsum (BIRCU, 2020)
The purpose of this study was to find out: (1) Development of power point-based learning media on Aqeedah Moral learning in MTs N Kisaran, (2) The feasibility of power point-based learning media on learning Aqidah Akhlak in MTsN Kisaran, (3) Practicality of learning-based media power point on the learning of Aqeedah Morals in MTs N Range, and (4) effectiveness of learning media based on power point on the learning of Aqeedah Morals in MTsN Kisaran in improving student learning outcomes. Research methods used by research and development methods (R&D). Product development procedures are carried out in stages: (1) potential and problems, (2) data collection, (3) product design, (4) validation, (5) product trials and (6) product revisions. The research findings show: (1) the development of power point-based learning media on Aqeedah Akhlak learning is done first by analyzing the needs and then proceed with the design of powerpoint media. The product produced as a learning medium that is used to facilitate students to learn, (2) the feasibility of power point-based learning media on Aqeedah Moral learning is done by material experts with a score of 83.33, a very valid category and a media expert with a score of 75.00 categories valid, so the cumulative score is 79.16 with a valid category, (3) practicality of power point-based learning media on Aqeedah Akhlak is done by conducting individual trials with a score of 80.83 very practical categories, small group trials with a score of 79.38 practical categories, and field group trials with a score of 89.75 very practical categories, so that when accumulated a score of 83.33 is obtained with a very practical category, and (4) the effectiveness of powerpoint-based learning media on Aqidah Moral learning in improving student learning outcomes obtained N scores -Gain 0.51 with the effective category so that it can be concluded that the powerpoint development product for learning the Morals is effective for enhancing student achievement.